Engineering threshold-based selection systems. Issue 9 (14th July 2021) - Pedone, Katherine H; González-Pérez, Vanessa; Leopold, Luciana E; Rasmussen, Neal R; Der, Channing J; Cox, Adrienne D; Ahmed, Shawn; Reiner, David J
Abstract: Using model organisms to identify novel therapeutic targets is frequently constrained by pre-existing genetic toolkits. To expedite positive selection for identification of novel downstream effectors, we engineered conditional expression of activated CED-10/Rac to disrupt Caenorhabditis elegans embryonic morphogenesis, titrated to 100% lethality. The strategy of engineering thresholds for positive selection using experimental animals was validated with pharmacological and genetic suppression and is generalizable to diverse molecular processes and experimental systems.